Echocardiographic Strain Evaluation Shows Persistent Echocardiographic Changes at 1 Year after Diagnosis of Multisystem Inflammatory Syndrome in Children - Jihye You (MDPI AG, 2024)
Coronavirus disease (COVID-19) is a global pandemic causing multisystem inflammatory syndrome in children (MIS-C). This study evaluated the long-term echocardiographic impact of MIS-C on patients and compared it with that in a healthy control group. Data from 22 children with MIS-C admitted to Jeonbuk National University Hospital and 22 healthy children (control group) were retrospectively analyzed. Echocardiographic data were compared at two distinct time points: diagnosis and 1-year follow-up. At diagnosis, the MIS-C cohort exhibited significantly reduced left ventricular ejection fraction (LVEF), longitudinal strain across the apical 4- and 2-chamber views, and global longitudinal strain (GLS). At 1-year follow-up, the reduced LVEF in the apical 4-chamber, overall longitudinal strain in the apical 4-chamber, and GLS persisted. However, the right ventricular free wall and global strain remained diminished compared with those in the control group. Despite significant changes over time, the LVEF and longitudinal strain in the apical 4-chamber and z-scores of all coronary arteries were normal at baseline and 1-year follow-up. Persistent cardiac alterations were observed in patients with MIS-C, particularly in both ventricular functions. Therefore, middle- to long-term echocardiographic follow-up may help improve understanding and management of long-term echocardiographic implications in patients with post-COVID-19 syndrome.